Research on Rough-Stem Culture Shredder - Корчак, М. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The aim of given publication is to analyze the experimental researches on grinder residues of rough-stem crops. When cultivating ground after harvesting rough-stem crops; the operation is complicated by rough-stem crops after cutting nearby root parts and stems; as a main object of cultivation isn’t only soil but plant rests that are grinded as well. Improvement in cultivation of field littered with plant rests of rough-stem crops after their harvesting are carried out by means of combined consecutive processes of influence upon plant residues and soil that allows to ensure: qualitative field cultivation; grinding and burying plant residues on the entire front of width gripping per a single aggregate passing; effective utilization of energy that is spent for drive of devices for grinding residues and thus to achieve the possibility for increasing the width of gripping of aggregate and its productivity; to make field surface. There was also elaborated power saving and ecologically effective technology of soil cultivation littered with plant residues of rough-stem crops; as well as a grinder for its realization. There was grounded a sequence of fulfillment and structure of technological processes of combined way in field cultivation littered with plant rests. The technology elaborated provides grinding and burying plant residues of rough-stem crops at effective energy utilization; that is spent for grinding; left levelled surface of field as it consists of combined technological processes of cutting and distributing of long and rough stems; compacting gathered mass; grinding plant residues together with the ground and levelling field surface. Processes of cutting and distributing long-and-rough plant residues are taken place in row widths where the processes of compaction; grinding and levelling in rows of sowings. Such sequence in carrying out the technological processes enables substantially reduce the power expenses and improve the cultivation quality. It identifies the factors that most affect the quality indicators grinder operation: depth of cultivation; milling drum speed; movement speed of the machine. As a result of analysis of experimental data justified rational values grinder modes; which provides a maximum degree of soil crumbling; fineness and degree of embedding plant rests. A technology of cultivation where soil is littered with rough-stem crops residues and a mincing machine (grinder) for its utilization with basing construction that ensures a qualitative power saving; ecologically effective and economy cultivation; as well as improves soil fertility with the method of grinding and with plant rests burying was found.